PHYSICAL EDUCATION AND SCHOOL LDB1: taking responsibility on law enforcement 10.639/03 and 11.645/08. - A. César Lins Rodrigues (Editora da Universidade de Santa Cruz do Sul, 2010)
This article backwards in its target the quarrel on the paper of the Pertaining to school Physical Education in the application of laws 10.639/03 and 11.645/08. Questionings on the "reasons" of the direction of a supposed obligation to the areas of Artistic Education and Brazilian Literature and History in detriment of the area of the Physical Education cover all the extension of the text, looking for, by means of forceful arguments, to search a reflection deeper regarding what, for however, it is judged to be a gap left for the law. Aspects as the relations ethnic-racial, construction of what it is personal in girls and boys not-whites, breach of the hegemonic speeches, politics of whiten in the periods daily pay and after-abolitionist and multicultural resume, all in the pertaining to school scope also are submitted, by means of developed provocative reflections throughout the writings. Key-words: Laws 10.639/03 and 11.645/08; School Physical Education; Relations Ethnic-Racial; Multicultural Curriculum.